Treading the beaten path with old and new obstacles: a report from the Indian HIPEC registry. (31st December 2018) - Bhatt, Aditi; Mehta, Sanket S.; Zaveri, Shabber; Rajan, Firoz; Ray, Mukurdipi; Sethna, Kayomarz; Katdare, Ninad; Patel, Mahesh D.; Kammar, Praveen; Prabhu, Robin; Sinukumar, Snita; Mishra, Suniti; et al.
Abstract: Background: The Indian HIPEC registry is a self-funded registry instituted by a group of Indian surgeons for patients with peritoneal metastases (PM) undergoing surgical treatment. This work was performed to Evaluate outcomes of cytoreductive surgery ± HIPEC in patients enrolled in the registry. Identify operational problems. Methods: A retrospective analysis of patients enrolled in the registry from March 2016 to September 2017 was performed. An online survey was performed to study the surgeons' attitudes and existing practices pertaining to the registry and identify operational problems. Results: During the study period, 332 patients were enrolled in 8 participating centres. The common indication was ovarian cancer for three centres and pseudomyxoma peritonei for three others. The median PCI ranged from 3 to 23. A CC-0/1 resection was obtained in 94.7%. There was no significant difference in the morbidity ( p = .25) and mortality ( p = .19) rates between different centres. There was a high rate of failure-to-rescue (19.3%) patients with complications and the survival in patients with colorectal PM was inferior. A lack of dedicated personnel for data collection and entry was the main reason for only 10/43 surgeons contributing data. The other problem was the lack of complete electronic medical record systems at all centres. Conclusions: These results validate existing practices and identify country-specific problems that need to be addressed. Despite operational problems, the registry is an invaluable tool for audit and research. It shows the feasibility of fruitful collaboration between surgeons in the absence of any regulatory body or funding for the project.